Realization of strong violet and blue emissions from ZnO thin films by incorporation of Cu ions. (March 2018) - Xu, Linhua; Xian, Fenglin; Zheng, Gaige; Lai, Min
Graphical abstract: For the Cu-doped ZnO thin films, two obvious changes are observed from the PL spectra. On the one hand, the UV emission centered at 382 nm disappears; on the other hand, a strong violet-blue co-emission occurs. Highlights: A strong blue-violet co-emission occurs after Cu ions are doped into ZnO thin films.. The violet emission centered at 430 nm is attributed to transitions of electrons from conduction band to Cu + acceptor levels. The blue emission centered at 470 nm is attributed to transitions of electrons from Cu 2+ donor levels to Cu + acceptor levels. Both the violet and blue emissions decrease when Cu-doping concentration is higher than 2 at.%. Abstract: In recent years, Cu-doped ZnO materials have attracted wide attention due to some unique properties, such as p-type conduction, room-temperature ferromagnetism and plentiful luminescence behavior. In this work, Cu-doped ZnO thin films with different doping levels were prepared by sol–gel method. The structural, morphological features and the composition of the samples were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray spectroscopy (EDX), respectively. The optical properties were analyzed by the UV–visible transmittance spectra and fluorescence spectra. The Cu-doping in a low concentration does not influence the crystal phase of wurtzite ZnO and has a very small impact on c-axis preferred orientation of ZnO thin films. With the increase of Cu-doping concentration, the Cu ions are gradually changed from dominant Cu + ions to dominant Cu 2+ ions. Cu-doping in a low concentration caused strong blue-violet emissions in ZnO thin films. The violet emission is attributed to the transition of electrons from the conduction band to Cu + acceptor levels, and the blue emission is ascribed to the transition of electrons from Cu 2+ donor levels to Cu + acceptor levels.